Is moderate hypofractionation accepted as a new standard of care in north america for prostate cancer patients treated with external beam radiotherapy? Survey of genitourinary expert radiation oncologists - McClelland III,Shearwood (2019)
ABSTRACT Introduction: Several recent randomized clinical trials have evaluated hypofractionated regimens against conventionally fractionated EBRT and shown similar effectiveness with conflicting toxicity results. The current view regarding hypofractionation compared to conventional EBRT among North American genitourinary experts for management of prostate cancer has not been investigated. Materials and Methods: A survey was distributed to 88 practicing North American GU physicians serving on decision - making committees of cooperative group research organizations. Questions pertained to opinions regarding the default EBRT dose and fractionation for a hypothetical example of a favorable intermediate - risk prostate cancer (Gleason 3 + 4). Treatment recommendations were correlated with practice patterns using Fisher's exact test. Results: Forty - two respondents (48%) completed the survey. We excluded from analysis two respondents who selected radical hypofractionation with 5 – 12 fractions as a preferred treatment modality. Among the 40 analyzed respondents, 23 (57.5%) recommend conventional fractionation and 17 (42.5%) recommended moderate hypofractionation. No demographic factors were found to be associated with preference for a fractionation regimen. Support for brachytherapy as a first choice treatment modality for low - risk prostate cancer was borderline significantly associated with support for moderate hypofractionated EBRT treatment modality (p = 0.089). Conclusions: There is an almost equal split among North American GU expert radiation oncologists regarding the appropriateness to consider moderately hypofractionated EBRT as a new standard of care in management of patients with prostate cancer. Physicians who embrace brachytherapy may be more inclined to support moderate hypofractionated regimen for EBRT. It is unclear whether reports with longer follow-ups will impact this balance, or whether national care and reimbursement policies will drive the clinical decisions. In the day and age of patient - centered care delivery, patients should receive an objective recommendation based on available clinical evidence. The stark division among GU experts may influence the design of future clinical trials utilizing EBRT for patients with prostate cancer.